1995
DOI: 10.1002/elan.1140070917
|View full text |Cite
|
Sign up to set email alerts
|

A solid composite pH sensor based on quinhydrone

Abstract: A solid composite pH sensor can be made from quinhydrone, solid paraffin and surface-modified graphite powder. It exhibits an almost theoretical slope of the potential-pH dependence (-57.7mV at 25"C), a formal potential Eo' = 0.6922V (vs. NHE), low standard deviations for repeated measurements (0.04 pH units), fast potential response (15 s) and a working range up to pH 9.5. The sensor can be used in moderately concentrated mineral acids and, unlike the conventional quinhydrone electrode, it is also applicable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

1997
1997
2019
2019

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 15 publications
0
21
0
Order By: Relevance
“…Also, E f E 1 E 2 a2. It has been shown previously that under potentiometric conditions the formal potential of solid quinhydrone in a graphite powder composite electrode is E f 0.692±0.058 pH V vs SHE [70]. So, at pH 2 the formal potential is E f 0.37 V vs Ag | AgCl | 3 M KCl.…”
Section: Resultsmentioning
confidence: 83%
“…Also, E f E 1 E 2 a2. It has been shown previously that under potentiometric conditions the formal potential of solid quinhydrone in a graphite powder composite electrode is E f 0.692±0.058 pH V vs SHE [70]. So, at pH 2 the formal potential is E f 0.37 V vs Ag | AgCl | 3 M KCl.…”
Section: Resultsmentioning
confidence: 83%
“…The cathodic and anodic peaks appear at 0.2 V and 0.32 V (vs. AgyAgCly3 M KCl), respectively, with a median at 0.26 V. This phenomenon was investigated previously [17], and it was shown that the median potential depended linearly on pH of the solution, with a slope of À59 mVypH. It was also demonstrated that this pair of peaks originated from the reversible reaction of the surface bound redox couple.…”
Section: Resultsmentioning
confidence: 89%
“…It has been shown in earlier studies [12], that composite electrodes based on quinhydrone are useful for calibration free measurements in solutions with pH values up to 8.5. These electrodes have the same properties as a conventional quinhydrone electrode but additionally they can be used in emulsions and they can be produced as very robust electrodes.…”
Section: Introductionmentioning
confidence: 97%